Classification of State Regulation Principles in the Field of Air Transport (Law and Safety, 2020)
It has been established that the principles of state regulation in the field of air transport can be defined as an objectively determined set of basic requirements, rules and standards, compliance with which is ensured by state coercive force, which are key guidelines for streamlining with the use of regulatory measures of public and legal relations between subjects and objects of aviation activity and provision of aviation services.It has been offered to classify these principles according to the following criteria: 1) direction of state regulation (in the field of air transport, in the field of airports and civil airfields activities, in the field of using aircraft, in the sphere of organization of air traffic and airspace, in the field of ensuring public order and safety in air transport, in the field of training aviation personnel); 2) scope of activity (general and special).It has been offered to include the rule of law, legality, economic validity (feasibility), adequacy, efficiency, balance of state influence (combination of legal and economic means of regulatory influence), predictability and transparency into the general principles of state regulation in the field of air transport. The content of these principles has been characterized.The significance and peculiarities of the observance of special principles of state regulation in the field of air transport (creation of equal conditions for the development of economic activity of air transport enterprises, social orientation, stimulation of national air producers, safety of air transportation, priority of environmental needs, principle of technical support) have been revealed.It has been concluded that the compliance with the principles of state regulation in the field of air transport will create a fundamental basis for sustainable development of the entire sector, introduce effective conditions for a free and competitive market of air services and air transportation in Ukraine, and ensure Ukraine’s participation in large international transport projects and complex international programs with preferential funding conditions. It has been offered to supplement the Air Code of Ukraine with the Art. 41 “Purpose, objectives and principles of state regulation in the field of air transport of Ukraine”.
Keywords: state regulation; principles; aviation sector; aviation transport; state support; system; regulatory influence